Combined Heart–Liver Transplantation in the MELD Era: Do Waitlisted Patients Require Exception Status?. Issue 3 (12th February 2014) - Schaffer, J. M.; Chiu, P.; Singh, S. K.; Oyer, P. E.; Reitz, B. A.; Mallidi, H. R.
Abstract Combined heart–liver transplant (HLT) is a viable therapy for patients with concomitant end‐stage heart and liver failure. Using data from the United Network for Organ Sharing database, we examined the cumulative incidences of transplant and mortality in waitlisted candidates for HLT, isolated heart transplant (HRT) and isolated liver transplant (LIV) in the Model for End‐Stage Liver Disease era. The incidence of waitlist mortality was higher in HLT candidates than in HRT candidates (p = 0.001, 26% vs. 12% at 1 year) or LIV candidates (p = 0.005, 26% vs. 14% at 1 year). These differences persisted after stratifying by disease severity. Posttransplant survival was not significantly different between HLT and HRT recipients or between HLT and LIV recipients. In a multivariable model, undergoing HLT was associated with enhanced survival for HLT candidates (hazard ratio, 0.41; confidence interval, 0.21–0.79; p = 0.008), but undergoing HRT alone was not. Interestingly, 90% of HLT recipients were allocated an organ locally, compared to 60% of HRT candidates and 73% of LIV candidates (both p < 0.001). These data suggest that the current cardiac and liver allocation systems may underestimate the risk of death for patients with concomitant end‐stage heart and liver failure on the HLT waitlist.